2021
DOI: 10.1177/0260106021996935
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of randomized controlled trials examining workplace wellness interventions

Abstract: Background: One of the influencing factors associated with weight gain is overeating as a maladaptive coping strategy to process or avoid the emotional impact of psychological stress. Psychological stress is chronically and pervasively associated with stress stemming from the workplace environment. Workplace wellness interventions have a unique opportunity to change environmental factors impacting psychological stress, which can improve individual food choice and weight management efforts. Aim: To synthesize e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…Specifically, intervention studies often utilize a control and intervention treatment that lacks randomization, with participants selfselecting their condition, or incorporate multiple interventions without the use of a control (Mhurchu et al, 2010). Intervention research presents randomization and control treatment as difficult to incorporate effectively due to limitations ranging from the sample size to the workplace setting (Mhurchu et al, 2010;Murphy et al, 2021). This research looks at the trends in research design and participant treatment to better understand their varying levels of rigour.…”
Section: Methodological Design Of Wellness Interventionsmentioning
confidence: 99%
“…Specifically, intervention studies often utilize a control and intervention treatment that lacks randomization, with participants selfselecting their condition, or incorporate multiple interventions without the use of a control (Mhurchu et al, 2010). Intervention research presents randomization and control treatment as difficult to incorporate effectively due to limitations ranging from the sample size to the workplace setting (Mhurchu et al, 2010;Murphy et al, 2021). This research looks at the trends in research design and participant treatment to better understand their varying levels of rigour.…”
Section: Methodological Design Of Wellness Interventionsmentioning
confidence: 99%
“…Advancing the rigour of the field relies on a greater prioritization of consistent measurement and methodology, like randomization and control treatment, otherwise the findings and its contribution may not be trusted (Murphy et al, 2021). The results indicated that while a quantitative, pre-post test, randomized controlled trial is somewhat of a golden standard, it was not always prioritized.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Consistent parameters that improve the likelihood of positive outcomes are unclear, due to the heterogeneity of exercise interventions [8]. However, longer and multifaceted programs appear more successful than shorter and unidimensional ones [8,21]. Despite a lack of consensus surrounding best practice and less than half of implemented interventions being successful, workplace exercise programs are still encouraged by governments and corporations as a part of general occupational health promotion [10,22].…”
Section: Introductionmentioning
confidence: 99%